Bioreactor design from an Obsolete Autoclave - Salazar-Rojas, Teresa (2014)
One of the known methodologies for solid waste treatment is bacterial decomposition in a controlled environment, under special and anaerobic conditions, inside an equipment called bioreactor. Equipment that represents an important inversion when it is required for continual and different substrates experiments. This article details the construction of a pilot bioreactor, with all the necessary requirement of functionality, from an obsolete autoclave. Given an example of how to extend the life of a “waste” and at the same time minimize costs getting an one hundred percent functional equipment from a obsolete devise.